2013
DOI: 10.3109/17435390.2013.829878
|View full text |Cite
|
Sign up to set email alerts
|

Nontoxic impact of PEG-coated gold nanospheres on functional pulmonary surfactant-secreting alveolar type II cells

Abstract: The outstanding properties of gold nanoparticles (NPs) make them very attractive for biomedical applications. In particular, the inhalation route has gained considerable interest as an innovative strategy for diagnosis and treatment of pulmonary diseases. It is, therefore, important to scrutinise the potentially deleterious or side effects of NPs on lung epithelium. The present study investigates, for the first time, the impact of polyethylene glycol (PEG)-coated NPs on freshly purified primary cultures of rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 67 publications
1
10
1
Order By: Relevance
“…Finally, this study’s results imply that there was a high degree of variability from one cell model to the next, and care must be exercised when choosing and interpreting the results from any one model. This is not unique to Ag as this has been reported with other ENM in similar cell models [23]. If possible, more than one cell model should be used to fully characterize any ENM biological impact.…”
Section: Discussionmentioning
confidence: 89%
“…Finally, this study’s results imply that there was a high degree of variability from one cell model to the next, and care must be exercised when choosing and interpreting the results from any one model. This is not unique to Ag as this has been reported with other ENM in similar cell models [23]. If possible, more than one cell model should be used to fully characterize any ENM biological impact.…”
Section: Discussionmentioning
confidence: 89%
“…6,11 In addition, in vitro studies by other groups generally showed only a slight effect of PEGylated AuNPs on various cell types (alveolar type II cells, macrophages, microglia). [29][30][31] However, the cell proliferation measured by the expression of the proliferation factor Ki-67 was inhibited to 60 % when the cells were exposed to 100 µg / mL PEGylated AuNPs for 24 hours (Figure 1 C). These data were supported by the determination of the cell number that was also reduced to 62 % compared to control cells under these conditions (Figure 1 D).…”
Section: Resultsmentioning
confidence: 99%
“…As a leading example, gold nanoparticles showed good biocompatibility in most cases and were considered to be a promising candidate in biomedical and preclinical applications. [23][24][25] Nonetheless, several investigations show considerable cytotoxicity of gold nanoparticles. [26][27][28] Does the dispersity of nanoparticles make a difference here?…”
mentioning
confidence: 99%